Implementation of Customer Relationship Management (CRM) at Giant Supermarket Pagar Alam Lampung WEB-Based - Hilda Dwi Yunita; Rudi Setiawan; Yodhi Yuniarthe (Universitas Nahdlatul Ulama Surabaya, 2022)
Giant Supermarket Pagar Alam Lampung is a company engaged in the sale of goods in Bandar Lampung. In marketing its products, it is still done by distributing sales catalogs and advertisements, so that many consumers cannot find out information about the stock of goods available at Giant Supermarket Pagar Alam Lampung. Consumers must come directly, if consumers want to get information or want to make purchases of goods, and do not improve sales and marketing strategies. CRM is a type of management that specifically discusses the theory of handling the relationship between a company and its customers, with the aim of increasing the value of the company in the eyes of its customers. CRM design will be discussed about ordering goods, purchase transactions, and service to consumers. The purpose and benefits of this research is to implement CRM in order to improve information services and customer satisfaction for Giant Supermarket Pagar Alam Lampung. The results of this study are a Customer Relationship Management (CRM) system in sales at Giant Supermarket Pagar Alam Lampung, this system can improve the company's service to customers through the sales provided, and this system can display information on goods sold, and can facilitate Giant Supermarket Pagar Alam Lampung in sales reporting.